IMPLEMENTASI UNDANG- UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DALAM UPAYA MELINDUNGI KEPENTINGAN ANAK - Nevey Varida Ariani (Jurnal Media Hukum, 2014)
Children  are  a mandate  from God Almighty which  in  them  laid  a  dignity  as human  beings.  Children  need protection against negative effects of a fast-growing developmnet. This essay is trying to discuss about how’s the  implementation of  the  law  of  SPPA  and  the  Government of  Indonesia’s  efforts  in protecting  children especially those who are conflicted with the law in accordance to The Law number 11 Year 2012. The method applied in this essay is qualitative socio-legal approach, based on the  library data. In the investigation process, prosecution  until  the  proceedings,  there  still  be diversion  process  Is  ultimately  enforced  considering  the children’s age and the penalties are not over than 7 years.  If this diversion process  is not applicable  then the judicial process is becoming ultimum remedium, putting the children in LPAS, LPAK and LPKS. Those institutions are  expected  to give  new hopes  to  children who’s dealing with  the  legal matters.  Through  the  approching system  in  Juvenile  Criminal  Court  Process  from  investigators, prosecutors,  judges,  advocates  to  the  public counselor, both  the Ministry of  Law  and Human Rights and  the  Social Ministry,  it  is  necessary  to establish  a clear  coordination  and  role  in  implementing  the  Juvenile Criminal Court  System.